2011
DOI: 10.1177/0194599811432103
|View full text |Cite
|
Sign up to set email alerts
|

Inner Ear Effects of Canal Wall Down Mastoidectomy

Abstract: In this study, CWD mastoidectomy without ossiculoplasty in the treatment of COM did not cause significant SNHL. In addition, using the DHI and THI measures, patient-perceived disability from dizziness and tinnitus, respectively, was shown to decrease after mastoid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Dizziness following mastoidectomy is a debilitating symptom. A report of 3 out of 34 patients developing dizziness after CWDM is reported by (15) John P Lionetti, while 7.5% developed Dix hall pike positive BPPV in our sample post operatively. Caloric effect following suction of cavity was noted around 54% (16) by Beutner Drik et al while our 's was for packing and suction 7.5% and 22.5% respectively which is well within reported range.…”
Section: Discussioncontrasting
confidence: 39%
“…Dizziness following mastoidectomy is a debilitating symptom. A report of 3 out of 34 patients developing dizziness after CWDM is reported by (15) John P Lionetti, while 7.5% developed Dix hall pike positive BPPV in our sample post operatively. Caloric effect following suction of cavity was noted around 54% (16) by Beutner Drik et al while our 's was for packing and suction 7.5% and 22.5% respectively which is well within reported range.…”
Section: Discussioncontrasting
confidence: 39%
“…1,8 Reports on SNHL caused by mastoidectomy (drilling) have been conflicting. 2,3,[10][11][12] We found that mastoidectomy status (yes or no) did not correlate significantly with the incidence of SNHL at 4000 Hz. Also, ossiculoplasty status (yes or no) did not significantly affect the likelihood of SNHL development (Table 4).…”
Section: Discussionmentioning
confidence: 63%
“…The titles were initially screened for inclusion resulting in further consideration of 485 publications. After screening of abstracts and then full‐text articles, 153 articles were selected for inclusion …”
Section: Resultsmentioning
confidence: 99%